Language and Education in Brazil: Linguistic Structural Problems and Their Historical Origins - O’Neill, Paul (Modern languages open, 2022)
In this article I offer an extended socio-historical overview of the Portuguese language in Brazil from independence to modern times in order to establish why there is such a gulf between the written official standard and actual linguistic usage. I reflect on how language is often regarded as a problem within educational contexts and how the response of academics in both linguistics and education studies has largely been focused on combating linguistic prejudice against non-standard varieties of Portuguese. I identify this as a recognition-oriented strategy aimed at changing attitudes towards non-standard forms of the language and its speakers and I question the effectiveness of such strategies. I argue that there are more fundamental structural problems with language and education in Brazil. These are identified as (a) the linguistic distance between the speech of the great majority of Brazilians and the official standard norm and (b) the uncertainty whether the education system is designed to teach this standard norm or, paradoxically, to assess the extent to which it is acquired. I conclude with an analysis of modern education policy documents where I find no strong emphasis for ensuring that students achieve active, advanced proficiency in the standard norm. I argue that recognition-orientated strategies need to be accompanied by strategies that advocate for structural changes in (a) the standard language to make it more readily resemble the actual speech of Brazilians and (b) how this standard is used as a means of instruction and assessment.   Para a versão em português clique no botão de download à direita.